Influence of Seasons and Extenders on Quality and Freezability of Gir Bull Semen under Middle Gujarat Climate - Chaudhari, DV; Patel, JA; Hadiya, KK; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was conducted to evaluate the seasonal influence (peak winter and summer) and the efficacy of three extenders (egg yolk based TFYG extender and egg yolk free soya bean based commercial extenders Optixcell and Andromed) on quality and freezability of Gir bull semen in Middle Gujarat. Semen ejaculates (6/bull/season, total 36) revealed mean ejaculate volume 6.49±0.30 ml, sperm concentration 1212.36±58.10 million/ml, progressive motility 74.17±0.78 %, live sperm 81.39±0.80 %, abnormal sperm 7.36±0.31 %, and sperm with intact plasma membrane 81.31±0.98 % and intact acrosome 94.81±0.24 %. Only the progressive sperm motility was significantly (P
Keywords: Gir bull; Season; Semen quality; Freezability; Post thaw longevity; Gujarat climate